Report on underground organization known as Al Fatah (Government publications and documents regarding Kashmir, 1948-1971, from the Indiana University, 1971)
This report on Al Fatah provides some history and background, while focusing on the events 1969-Jan. 1971, on the leader of the organization, Ghulam Rasool Zahgir, and his associates.